Media pembelajaran kontekstual dalam pendidikan matematika di indonesia: Tinjauan sistematis - Dewi Tarisa Putri; Majid Majid; Emli Rahmi (IKIP Siliwangi, 2026)
Contextual learning has become an important approach in mathematics education. This study aims to analyze research trends, implementation, impacts, and challenges in the use of contextual learning media in mathematics education in Indonesia. In addition, this study identifies the characteristics of contextual learning media used in mathematics learning. This research employed a Systematic Literature Review (SLR) method using the PRISMA 2020 guidelines. The data were obtained from the Scopus database covering the 2020–2025 period using the Boolean keywords “Learning Media AND Math* AND Indonesian”. The research stages included article identification, screening, eligibility assessment based on inclusion and exclusion criteria, and synthesis of selected articles. Reference management was supported by Publish or Perish, Mendeley, Zotero, and Microsoft Excel. The findings show that contextual learning media have developed through local culture-based approaches and interactive digital technology. These media improve student engagement, mathematical literacy, mathematical communication, critical thinking, and conceptual understanding. However, their implementation still faces challenges related to teacher readiness, media integration, and diverse student characteristics.